Working together for the inclusion of immigrant pupils A case study of a rural community in Iceland - Hafdis Guõjónsdótti; Anna Katarzyna Wozniczka (University of Aberdeen, School of Education, 2019)
Global migration brings new challenges and opportunities for schools, as they are becoming more diverse in terms of pupils' mother tongues, ethnicities, religions, and sociocultural resources. In case of Iceland, this is a relatively new reality. While there has been some research with immigrant pupils internationally, most studies focus on urban areas. This article reports on a case study in a rural compulsory school in Iceland. The research question was: How does a rural school understand and work for inclusion and participation of immigrant pupils? Indepth interviews with immigrant pupils and their teachers together with observations were applied. The simultaneous thematic analysis included coding of the data and sorting it into themes by discovering recurrent routines and interaction patterns. The concepts of inclusion and local agency were used as a theoretical framework. Findings suggest that teachers are the key agents in inclusion of immigrant pupils. Despite lack of extensive experience or special agenda regarding immigrant pupils, the teachers and school principal manage to involve all pupils in the process of learning. Moreover, the support of local municipality and caring relations with the school personnel have a positive impact on pupils' feeling of belonging and encourage their participation.